USING SOME TREATMENTS TO IMPROVE VEGETATIVE GROWTH CHARACTERISTICS OF THREE GRAPE CULTIVARS - N. A. Oudah; S. A. A. Saleh (مجلة الأنبار للعلوم الزراعية)
The study was conducted in research station in Al-Bu'itha area Belong to College of Agriculture - University of Anbar during growing season 2023 on Three grape Cultivars, Black Hamburg, Kamaly, and Zytuny, 3 years old, to investigate the effect of adding Nanofertilizer NPK at concentrations (0, 10, 15 and 20 g Plant-1 and adding Humic acid at two concentrations (0 and 100 g Plant-1) in characteristics of vegetative growth, A factorial experiment was carried out according to a split -split plot design with three replicates, The results showed significant superiority to the Humic acid addition treatment at a concentration of 100g plant-1 in percentage of dry matter in leaves, stem diameter, length of mature part of canes, ratio of mature wood to total wood of and number of main branches and  leaves  Chlorophyll content of, The treatment of adding NPK Nanofertilizer at a concentration of 20g plant-1 also had a positive effect on all traits studied, As for three Cultivars, there were significant differences in Vegetative growth characteristics and leaves chlorophyll content, except for leaves dry weight percentage, As for the two- and three interactions between study factors, there were significant differences in most of the traits studied.